(untitled) (Praxis Educativa, 2012)
The Priority Learning Nucleus (PLN) prescribed by the Cultural and Education Federal Council (CEFC) move us to an apparently simple question: Are our students learning those contents? We start to work from the hypothesis that there are notions of personal and social relevance that have never been learnt. It is what we call “blanks in learning”, or contents that have been learned with mistakes, what we call “mistakes induced from an irrelevant teaching”. Our aims are: to test the PLN of Elementary School with students learning History at High School; to analyze the coherence between teaching and the Basic Principles of General Didactics; to understand those factors that obstruct learning and make students commit mistakes. Our methodology was focused on testing, from an intentional sample, several hundreds of students in Santa Rosa and other cities from La Pampa and to interview their teachers. Between 60 and 80% of these students haven’t got the PL. We have detected distortions in teaching: learning has not been guarded through evaluation; opportunities have not been given to consolidate learning; recurrence has not been considered; sequences of learning have been altered hindering understanding. These characteristics of irrelevant teaching are connected with differences between Special Didactics and General Didactics. When we teach we can be responsible for wrong conceptual constructions. Only investigations in which General and Special Didactics work related can help us assure teaching in conditions of equality, recognizing differences to avoid mechanisms of exclusion at school. In this way, we will be respecting our students’ right to learn.